Analysis of English Course Program Management at the BBC Stabat English Course Institute - Sihaloho, Michelle Josua; Saragih, Mahfuzi Irwan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The purpose of this study is to analyze the management of the English course program at the BBC Stabat institution, to describe and interpret the factors that influence the management of the English course program at the BBC Stabat course institution. This study uses a qualitative research method. The subjects of this study were the head of the institution, the English coordinator, the English tutor, and one of the English course students at the BBC Stabat English course. Determination of subjects was carried out using purposive sampling techniques. Data collection was carried out using observation, interview and documentation techniques. The techniques used in data analysis are data reduction, data presentation and drawing conclusions. The technique used to explain the validity of the data is by using triangulation of sources and techniques. The results of this study indicate that: (1) The management of the English course program carried out by the BBC Stabat English course goes through several stages, namely planning which is carried out by planning administration and learning programs; organizing by creating an organizational structure and division of labor; implementing an English course program through a staged test of ability tests to increase the level of the student's ability class; supervision through meetings and accountability reports and evaluating the program. (2) Supporting factors are: (a) Quality of teaching; (b) Flexibility in learning; (c) Strong management support; (d) Effective team communication. (3) Inhibiting factors that affect management are disruption of technological infrastructure and differences in student characteristics.